Frontispiece: The Methylsulfonyloxyl Radical, CH3SO3. Issue 39 (18th September 2015) - Zhu, Bifeng; Zeng, Xiaoqing; Beckers, Helmut; Francisco, Joseph S.; Willner, Helge
Abstract : Atmospheric Chemistry . In their Communication on page 11404 ff., H. Beckers et al. report the isolation of methylsulfonyloxyl radicals, key intermediates in the atmospheric oxidation of dimethyl sulfide.